(untitled) (Bangladesh Journal of Urology, 2022)
Introduction: This study is an effort to develop an alternative to available graft sources for complex and long-segment strictures. For this to assess the outcome of harvesting a full-thickness abdominal skin graft for urethral reconstruction we conducted this study. Material and Method: The study was prospective type of observational study. Data were collected between June 2019 and November 2021 from patients underwent urethroplasty using full thickness skin grafts harvested from abdominal skin. Result: Total 16 patients followed up. Mean stricture length was 8 + 3.38 cm (range 5-12 cm). The aetiology [Figure 2] of urethral stricture included urethritis (6 patients), urethral trauma (7 patients), failed hypospadias repair (2 patient) and unknow (1 patient). The mean prepared graft length was 8.68 + 4.58 cm (range 7–14 cm), the mean operation time was 86.45 + 30.28 minutes (range 55 –130 minutes). Median follow-up was 24 months. 2 patients developed febrile urinary tract infections requiring oral antibiotics. 1 patient with history of urethritis developed recurrent stricture. So overall success rate is 93.75% with p value of < 0.001; that is statistically significant. Conclusion: Selective use of abdominal skin grafts may be well suited for patients with long-segment urethral strictures in one or two stages when other graft sources are not available or feasible. Bangladesh J. Urol. 2021; 24(2): 175-180